A RELATION BETWEEN WEB PAGES - DORU ANASTASIU POPESCU (Challenges of the Knowledge Society)
In this paper we define a relation on the set of web pages from a web application. With the help of this relation, we obtain a partition of this set into subsets. Verifying and testing the web application will be accomplished by testing only one representative in each subset. We present two algorithms, one for verifying the relation between two web pages and one for determining which pages to test.